Estudo morfológico do hipocampo de uma espécie de primata da Amazônia: Cebus apella, (Linnaeus, 1758) - Torres, Laila Brito [UNIFESP] (2010)
The nonhuman primates constitute irreplaceable animal models for research areas in which their close evolutionary relationship to humans ensures high fidelity models with predictive and discriminative abilities that may not be available in other species. The Cebus apella, a New World primate specie belonging to the Cebidae family, Cebinae suborder (Linnaeus, 1758) are commonly used in biomedical and behavior research being the specie of choice for many cognitive experimental tasks. The hippocampus, a highly plastic limbic structure situated in the temporal lobe is important for learning and memory consolidation. In this way, the aim of this study was to characterize quantitatively and qualitatively the Parvalbumin positive cells in the hippocampal formation of the Cebus monkey and also estimate the volume and neuronal number in their different subfields using an optical fractionator design method. The results obtained in our study will be useful for many experimental designs in translational medicine.